1984
DOI: 10.1111/j.1432-1033.1984.tb08174.x
|View full text |Cite
|
Sign up to set email alerts
|

Catabolite repression in yeasts is not associated with low levels of cAMP

Abstract: The relationship between levels of CAMP and catabolite repression in yeasts has been investigated. Strains of Succharomyces cerevisiae, Schizosaccharomyces pomhe and Kluyuerornyces jrugilis were used. The yeasts were grown on different carbon sources to attain various degrees of repression. Galactose repressed as much as glucose, while maltose was less effective. Full derepression was achieved with ethanol.The enzymes tested were fructose-bisphosphatase, malate dehydrogenase, glutamate dehydrogenase (NAD depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
4

Year Published

1989
1989
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 44 publications
2
53
2
4
Order By: Relevance
“…Surprisingly, these exponential cells on glucose (whether heat stressed or not) did not show any increase in neutral trehalase activity after phosphorylating the crude extract with an ATP/cAMP mixture (Table 1), in contrast to a 2 4 times increase in neutral trehalase activity in stationary cells grown on glucose or exponential cells grown on galactose [17]. We do not have a definite explanation for this, however, it could be related to the finding that c A M P levels of exponential cells growing on glucose are high when compared to stationary cells [25,26]. Furthermore, as shown in Table 1, we could not detect any significant acid trehalase activity either from heat stressed or non-heat stressed exponentially growing cells, thereby supporting our finding that the ATH1 gene is not involved in the recovery of cells after heat shock in contrast to the NTH1 and YBR0106 genes.…”
Section: Neutral and Acid Trehalase Activity At Heat Stresscontrasting
confidence: 41%
“…Surprisingly, these exponential cells on glucose (whether heat stressed or not) did not show any increase in neutral trehalase activity after phosphorylating the crude extract with an ATP/cAMP mixture (Table 1), in contrast to a 2 4 times increase in neutral trehalase activity in stationary cells grown on glucose or exponential cells grown on galactose [17]. We do not have a definite explanation for this, however, it could be related to the finding that c A M P levels of exponential cells growing on glucose are high when compared to stationary cells [25,26]. Furthermore, as shown in Table 1, we could not detect any significant acid trehalase activity either from heat stressed or non-heat stressed exponentially growing cells, thereby supporting our finding that the ATH1 gene is not involved in the recovery of cells after heat shock in contrast to the NTH1 and YBR0106 genes.…”
Section: Neutral and Acid Trehalase Activity At Heat Stresscontrasting
confidence: 41%
“…However several lines of evidence indicate that, in yeast, catabolite repression is not associated with a low level of CAMP. In a mutant permeable to CAMP, the addition of exogenous cAMP did not prevent glucose repression of galactokinase synthesis (Matsumoto et al, 1982) and in different yeasts intracellular concentrations of cAMP are higher in the presence of glucose and other sugars than in derepressed conditions (Eraso and Gancedo, 1984). Results from strains lacking adenylate cyclase suggest that, in S. certvisiae, cAMP itself does not play a critical role in catabolite repression (Matsumoto et al, 1983a) although cAMP may be necessary for the transcription of certain genes like SUC2 (Matsumoto et al, 1984).…”
Section: The Signalmentioning
confidence: 80%
“…The synthesis of this enzyme is also repressed by glucose (Eraso and Gancedo, 1984) and this repression appears to depend on the presence of a repressing nitrogen source like glutamine (Coschigano et al, 1991). The cyc8 mutation allows a partial derepression of GDH2 in the presence of glucose but neither HXK2 nor HAP3 or HAP4 appear to be involved in its regulation; other regulatory mutants which affect other systems subject to catabolite repression have not been tested.…”
Section: Nad-dependent Glutamate Dehydrogenasementioning
confidence: 99%
See 1 more Smart Citation
“…Krug et al (2005) reported that the increased aconitase activity of cells grown on acetate is partially because of decreased repression by AcnR and that an additional transcriptional regulator (besides AcnR) or another regulatory mechanism for aconitase might exist. The only regulatory system that has ubiquitous effects on many different genes is catabolite derepression by cAMP receptor protein (Eraso & Gancedo, 1984;Kolb et al, 1993;. This regulator activates many genes in the presence of acetate.…”
Section: Discussionmentioning
confidence: 99%